At the Outer Limits of Language: Mallarmé's Un Coup de dés and Huidobro's Altazor - Nancy B. Mandlove (Studies in 20th & 21st Century Literature, 1984)
While it is quite possible that Un Coup de dés served Huidobro directly as a formal, thematic and linguistic model for Altazor, the essential connection between the two poems lies in a parallel effort to repeat the act of the original Creation. To this end, both rely on basic archetypal patterns, resulting in parallel thematic development. These archetypal patterns are created not only themati-cally, but also linguistically. The fall, destruction and resurrection of Adam and Orpheus is simultaneously the fall, destruction and resurrection of language. Huidobro has taken up the challenge of Mallarmé to spin out of nothingness the abyss, the primordial sea of potential in which all reality is dissolved, another constellation/poem, which is at once the same and unique, another configuration of the eternal Poem: a parallel Orphic explanation of the earth. Both poems push language to the outer limits in an attempt to return to the original, Edenic language—the language of Adam and of Orpheus.
Keywords: Un Coup de dés; Huidobro; Altazor; poem; Creation; archetypal; linguistically; fall; destruction; resurrection; Adam; Orpheus; language; Mallarmé; constellation